Optimation of Nanocream 3,4-dimethoxychalcone as UVA Protection Agent Used Simplex Lattice Design Method - erlina fatmasari (Health Media, 2022)
3,4-dimethoxychalcone (3,4-DMT) is a chalcone derivative can be used as a UVA-protection agent but its insolubility in water (log-P 3.84). Therefore, an appropriate delivery system is needed that can increase the solubility and transport of 3.4 DMT through the skin layer. The nanocream formulation was chosen to make chemical sunscreen preparations suitable for water insoluble ingredients. This study aims to obtain the optimal composition of 3,4-DMT in a nanocream formula. Nanocream formulation was carried out using the simplex lattice design method. VCO was used as the oil phase with a mixture of tween 80 and span 80 (Smix) which was mixed using a high-energy-emulsification method. Physical test of nanocream such as pH, spreadibility, viscosity, adhesion, freeze thaw showed result good result and particle size > 200 nm, zeta potential ± 30 mV, PDI < 1; drug content 94.02%-94.90%. Data analysis for all measurements used ANOVA statistical analysis.